A new species and new records of Sericini chafers from the Lower Gangetic Plains in India (Coleoptera: Scarabaeidae: Sericinae) - Bhunia, Debika; Gupta, Devanshu; Sarkar, Subhankar Kumar; Ahrens, Dirk (Zootaxa, 2023)
Here, we investigated the diversity of Sericini in the faunistically rather unknown Lower Gangetic plains in North India, based on material from the collection of the Zoological Survey of India. We discovered one new species from West Bengal, Maladera kolkataensis Bhunia, Gupta, Sarkar & Ahrens, and provide further records of an additional 23 species belonging to five genera from the lowlands of the states Bihar and West Bengal. Out of these, 21 species represent new state records: 12 for Bihar and nine for West Bengal. All recorded species are briefly documented by diagnostic illustrations.